A Novel Lysolecithin Model for Visualizing Damage in vivo in the Larval Zebrafish Spinal Cord - Morris, Angela D.; Kucenas, Sarah (Frontiers in Cell and Developmental Biology, 2021)
Background: Lysolecithin is commonly used to induce demyelinating lesions in the spinal cord and corpus callosum of mammalian models. Although these models and clinical patient samples are used to study neurodegenerative diseases like multiple sclerosis (MS), they do not allow for direct visualization of disease-related damage in vivo. To overcome this limitation, we created and characterized a focal lysolecithin injection model in zebrafish that allows us to investigate the temporal dynamics underlying lysolecithin-induced damage in vivo. Results: We injected lysolecithin into 4 to 6 days post fertilization (dpf) zebrafish larval spinal cords and coupled with in vivo, time-lapse imaging, observed hallmarks consistent with mammalian models of lysolecithin-induced demyelination, including myelinating glial cell loss, myelin perturbations, axonal sparing, and debris clearance. Conclusions: We have developed and characterized a lysolecithin injection model in zebrafish that allows us to investigate myelin damage in a living, vertebrate organism. This model may be a useful pre-clinical screening tool for investigating the safety and efficacy of novel therapeutic compounds that reduce damage and/or promote repair in neurodegenerative disorders like MS.